Evaluation of cardiac hypertrophy in the setting of sudden cardiac death - Kristopher S. Cunningham; Danna A. Spears; Melanie Care (Oxford University Press, 2019)
Ventricular hypertrophy is a common pathological finding at autopsy that can act as a substrate for arrhythmogenesis. Pathologists grapple with the significance of ventricular hypertrophy when assessing the sudden and unexpected deaths of young people and what it could mean for surviving family members. The pathological spectrum of left ventricular hypertrophy (LVH) is reviewed herein. This article is oriented to the practicing autopsy pathologist to help make sense of various patterns of increased heart muscle, particularly those that are not clearly cardiomyopathic, yet present in the setting of sudden cardiac death. The article also reviews factors influencing arrhythmogenesis as well as genetic mutations most commonly associated with ventricular hypertrophy, especially those associated with hypertrophic cardiomyopathy (HCM).